3D micro-combs self-assembled from 2D N-doped In2S3 for room-temperature reversible NO2 gas sensing. (March 2022) - Cheng, Yinfen; Li, Zhong; Tang, Tao; Xu, Kai; Yu, Hao; Tao, Xuewei; Hung, Chu Manh; Hoa, Nguyen Duc; Fang, Yuqiang; Ren, Baiyun; Chen, Hui; Ou, Jian Zhen
Highlights: A 3D micro-comb structure was self-assembled from 2D N-doped In2 S3 nanoflakes. N dopants were inserted into the host during exfoliation of In2 S3 microspheres. N dopants induced a n - to p-type transition of In2 S3 with excitation-dependent PL. The micro-comb exhibited a reversible NO2 sensing performance at room temperature. Visible light excitation improved the response kinetics and detection limit of NO2 sensing. Abstract: Two-dimensional (2D) metal sulfides have been an emerging material group for high-performance and power-saving gas sensing. However, relatively little attention is paid to developing doping-driven approaches to improve their gas interaction properties, particularly at room temperature. In this work, we realize room-temperature reversible NO2 gas sensing by utilizing the three-dimensional (3D) micro-combs self-assembled from 2D N-doped In2 S3 . Specifically, hydrothermal synthesized In2 S3 microspheres as the initial material are exfoliated down to 2D single-unit-cell-thick (∼3 nm) nanoflakes in the presence of ultrasonic force, while the N dopants are inserted into the crystal lattices simultaneously. The N dopants significantly modify the electronic band structure of In2 S3 to facilitate the hybridization with NO2 molecular orbitals, induce an n- to p- type transition, decrease the surface activation energy, and activate the strong excitonic interaction property. The 3D N-doped In2 S3 micro-combs exhibit a response magnitude of 15% for 10 ppm NO2 at room temperature with complete recovery, high selectivity, and excellent repeatability, while incorporating blue light excitation further increases the response magnitude and shortens the response/recovery time, which are rarely seen in 2D metal sulfides. This work demonstrates the possibility of implementing 2D doped metal sulfides and their derivatives for high-performance room temperature gas sensors. Graphical abstract: Image, graphical abstract